Politics of Hospitality, Peace and Tourism: Review and Analysis - Kunwar, Ramesh Raj; Khanal, Aaditi (Journal of Tourism and Hospitality Education, 2018)
The hospitality has been discussed only in the model of social, private and commercial domain. It has been argued that there are two school of thoughts: one sees the host-guest relationship entirely based on the commercial transaction between them and another sees hospitality as a social phenomenon. This paper highlights the correlation between hospitality, peace and tourism with context to the behaviors of nationstates as political actors towards migrants, asylum seekers and refugees in terms of ethics, human rights and citizenship with special focus on the difference in approach of hospitality between the rich and poor countries. However, it is also evident that peace can only be achieved through the acceptance of the outsiders without prejudices, although this has been rejected by the thinkers who believe that it is impossible for any nation to fully welcome the guests which will require them to compromise their national sovereignty. Attention has been given to the concept of hospitality with special reference to Kant’s thought of universal hospitality, Levinas’s concept of the ethics and politics of hospitality, and Derrida’s notion of absolute or unconditional and conditional hospitality. The issues thus discussed are the various forms of discrimination in terms of the hospitable behaviors by the hosts (nations) towards the guests (migrants) by analyzing the host-guest relationship and further reflecting it upon the current global political scenario. Journal of Tourism and Hospitality Education 8 (2018) 1-29